2021
DOI: 10.3389/fmolb.2021.673044
|View full text |Cite
|
Sign up to set email alerts
|

Altered Glycosylation in the Aging Heart

Abstract: Cardiovascular disease is one of the leading causes of death in developed countries. Because the incidence increases exponentially in the aging population, aging is a major risk factor for cardiovascular disease. Cardiac hypertrophy, fibrosis and inflammation are typical hallmarks of the aged heart. The molecular mechanisms, however, are poorly understood. Because glycosylation is one of the most common post-translational protein modifications and can affect biological properties and functions of proteins, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 63 publications
1
13
0
Order By: Relevance
“…High levels of core fucosylation were maintained in healthy NC‐rich NP tissue during maturation which was an unexpected finding considering that core fucosylation is arguably affected with aging 38,39 . Core fucosylation is involved in conditions such as cancer, 40–42 cardiac regenerative capacity, 43 liver disease, 44 and autoimmune diseases, 45 potentially through disruption of cell recognition, signaling, and adhesion 46,47 .…”
Section: Discussionmentioning
confidence: 93%
“…High levels of core fucosylation were maintained in healthy NC‐rich NP tissue during maturation which was an unexpected finding considering that core fucosylation is arguably affected with aging 38,39 . Core fucosylation is involved in conditions such as cancer, 40–42 cardiac regenerative capacity, 43 liver disease, 44 and autoimmune diseases, 45 potentially through disruption of cell recognition, signaling, and adhesion 46,47 .…”
Section: Discussionmentioning
confidence: 93%
“…We recently showed that hyperglycosylation of proteins is correlated with increased plasma mannose levels ( 2 ). Moreover, we showed that increased GMPPB levels correlate with protein hypermannosylation and enhanced plasma mannose levels ( 24 ). Altered glycosylation may affect protein stability and conformation, protein interactions and adhesion, as well as protein activity and localization ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Membranes were blocked in 2% BSA for 1 h at RT and incubated with primary antibodies at appropriate dilutions in tris-buffered saline supplemented with 0.1% Tween-20 (TBS-T) overnight at 4°C. The following primary antibodies were used: rabbit anti-GMPPA (#15517-1-AP, Proteintech, Rosemont, IL, USA) 1:500, rabbit anti-GMPPB (#15094-1-AP, Proteintech, Rosemont, IL, USA) 1:500, rabbit anti-GAPDH (#10494-1-AP, Proteintech, Rosemont, IL, USA) 1:1,000, self-made mouse anti-oligomannose antibody (6–9 terminal mannose residues) 1:50 [gift of Rüdiger Horstkorte, Halle ( 24 )]. Membranes were washed in TBS-T and primary antibodies were detected with horseradish peroxidase-conjugated secondary antibodies in an appropriate dilution.…”
Section: Methodsmentioning
confidence: 99%
“…Changes in the glycoproteome probably contribute to the age -related functional decline of the cardiovascular system as well as the heart and the aorta performance. 43, 44 Glycans covering the surface of EVs form a corona that has been recognized as a crucial mediator of EV functions. 45,46 Glycomic profile of melanoma--derived ectosomes showed important correlation with melanoma malignancy.…”
Section: What Do Extracellular Vesicles Contain?mentioning
confidence: 99%